Verbal aptitude hurts children's economic decision‐making accuracy. (17th August 2020) - Bruyneel, Sabrina; Cherchye, Laurens; Cosaert, Sam; De Rock, Bram; Dewitte, Siegfried
Abstract: The impact of children's decision making increases with age and has relatively increased through time. Although a lot is known about cognitive development, less is known about how this development impacts decision accuracy in economic situations. This study builds on revealed preference theory to study the impact of cognitive aptitude on economic decision‐making accuracy and explores the intervening role of decision heuristics. In a study ( n = 100) where children from three age groups had to make choices between combinations of products, we found that decision accuracy was lower for kindergarteners than for children from the third and sixth grade, replicating and validating older findings. We found that one aspect of cognitive aptitude, namely, verbal aptitude, hurts rather than helps decision accuracy. Further explorations suggested that this relation was due to the decreased use of the "more is better" heuristic, a child's preference for options with many units, which decreased with increasing verbal aptitude but increased rational decision making. We discuss the implications of the negative effect of verbal aptitude on economic decision‐making accuracy.